Increased frequency of integrons and β-lactamase-coding genes among extraintestinal Escherichia coli isolated with a 7-year interval - Mokracka, Joanna (Springer Netherlands, 2012)
We analyzed the level of antimicrobial resistance, and the presence of integrons and β-lactamase-coding genes in 69 clinically relevant Escherichia coli strains originating from extraintestinal infections isolated in 1999–2001 and 2008–2010. Comparison of the two groups showed significant differences in drug resistance frequency, and the presence of integron and β-lactamase-coding genes. The frequency of resistance to all antimicrobials beside imipenem, streptomycin, piperacillin/tazobactam, and sulfamethoxazole increased significantly, especially towards aminoglycosides, β-lactams and fluoroquinolones. Similarly, we noticed an increase in the number of strains with integrons from 31.6 to 80.7 %. The presence of integrase genes was associated with elevated frequency of resistance to each antimicrobial tested besides imipenem, piperacillin/tazobactam and ceftazidime. The presence of integrons was also associated with multidrug resistance phenotype. The genetic content of integrons comprised genes determining resistance toward aminoglycosides, sulfonamides and trimethoprim. Moreover, we noticed a significant increase in the frequency of bla (CTX-M) β-lactamases, with appearance of bla (CTX-M-15) variant and newer plasmid-encoded β-lactamases like CMY-15 and DHA. The emergence of strains resistant to several classes of antimicrobials and carrying integrons, ESBL and AmpC β-lactamase-coding genes may predict the spread of isolates with limited treatment options. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10482-012-9797-9) contains supplementary material, which is available to authorized users.